An absorbable anal fistula repair assembly and methods of making and using the same
By using a staged release anal fistula repair component, which combines biodegradable materials and medications, the long treatment cycle and complicated surgery of perianal fistula type in Crohn's disease are solved, achieving efficient anal fistula repair and infection prevention, and improving patients' quality of life.
Patent Information
- Application Number
- CN202510987027.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-17
- Publication Date
- 2026-02-03
- Estimated Expiration
- 2045-07-17
AI Technical Summary
In the existing technology, drug treatment for Crohn's disease perianal fistula type (pfCD) has a long cycle, slow effect and recurrence, and surgical treatment is complicated and prone to infection, which affects the patient's quality of life.
An anal fistula repair component made of biodegradable materials promotes anal fistula healing by releasing regenerative repair regulators, immunomodulators, and antibiotics in stages, thereby achieving phased degradation and drug release.
It improves the repair effect of anal fistula, reduces the risk of infection, simplifies the treatment process, and enhances the patient's quality of life and physical and mental health.
Smart Images

Figure CN120531943B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of biomedical materials technology, and relates to absorbable anal fistula repair catheters, specifically an absorbable anal fistula repair catheter, its preparation method, and its application. Background Technology
[0002] Crohn's disease (CD) is a chronic, nonspecific inflammatory bowel disease with an unclear etiology and pathogenesis. In recent years, its incidence in my country has increased significantly. Perianal fistulizing Crohn's disease (pfCD) refers to a form of Crohn's disease that involves the perianal area, forming fistulas. The incidence of pfCD in Crohn's disease patients is as high as 17%-43%.
[0003] In existing technologies, drug and surgical treatments are the main methods for treating pfCD. Treatment drugs are divided into non-biological agents and biological agents: Infliximab (IFX) is generally recommended as a first-line treatment for complex anal fistulas; non-biological agents mainly include glucocorticoids, antibiotics, immunosuppressants, aminosalicylic acid (5-ASA) and its prodrugs, as well as enteral nutrition. While glucocorticoids can control intestinal inflammation, they may worsen pfCD symptoms and increase surgical risks. The American Gastroenterological Association (AGA) states that glucocorticoids are ineffective in treating pfCD. Although large-scale controlled studies on antibiotics are lacking and the quality of evidence is relatively low, most experts support ciprofloxacin and metronidazole as first-line antibiotics for treating pfCD, helping to improve symptoms; however, their use alone rarely promotes fistula healing. Immunosuppressants help promote fistula closure and maintain remission in pfCD, but their onset of action is slow; adverse reactions are relatively common, requiring close monitoring during use. Currently, no studies support the effectiveness of 5-ASA and its prodrugs in treating pfCD. 5-ASA enemas or suppositories may help improve perianal symptoms of pfCD. Enteral nutrition can induce remission of intestinal symptoms in CD, but its efficacy in pfCD has only been reported in a few cases. However, in drug treatment, whether using biological or non-biological agents, the treatment cycle is long, requiring repeated or repeated administration, with slow efficacy or relapse; patients suffer greatly, experiencing low quality of life and psychological distress.
[0004] Surgical treatment is more common in patients with severe symptoms. For patients with perianal fistula (PFCD), if a perianal abscess is present, and the abscess is large or deep, incision and drainage may be necessary. During the procedure, the doctor will make an incision at the point of greatest fluctuation in the abscess or around the external opening of the rupture, depending on the specific condition of the abscess, and place a catheter to drain the pus. Catheter placement helps reduce local inflammation, prevent abscess recurrence, promote fistula healing, improve the patient's quality of life, and reduce the rate of rectal resection. With surgical treatment, i.e., drainage seton placement, the wound remains open, making it prone to infection. Throughout the treatment process, the daily cleaning, dressing changes, debridement, and disinfection are very tedious for the patient, causing varying degrees of impact on their physical and mental health, quality of life, and daily work. Summary of the Invention
[0005] This invention addresses the shortcomings of existing technologies and practical needs by providing a staged absorbable anal fistula repair component, its preparation method, and its application, based on the characteristic that biodegradable materials can degrade in vivo.
[0006] The first objective of this invention is to provide an anal fistula repair component; the second objective is to provide a method for preparing the anal fistula repair component; the third objective is to provide a method for using the anal fistula repair component; the fourth objective is to provide an anal fistula repair material, wherein the anal fistula repair material is an absorbable anal fistula repair body obtained by using the above-described anal fistula repair component and the above-described method of use; and the fifth objective is to provide the application of the anal fistula repair component in the preparation of instruments and drugs for treating anal fistulas.
[0007] The technical principle of this invention is as follows:
[0008] The various layers of the anal fistula repair component are made of biodegradable materials. Through comprehensive design of the material structure, molecular weight, layer thickness, pore size and porosity, and manufacturing process, the degradation of each layer is achieved in stages to meet the clinical needs during the anal fistula repair process. Furthermore, by loading regenerative repair regulators, immunomodulators, and antibiotics onto each layer, the corresponding drugs or preparations are released as each layer degrades from the outside to the inside, according to the recovery cycle of the anal fistula, thereby improving the anal fistula repair effect.
[0009] Because the fistula repair component consists of individual layers that are then rolled up to form an absorbable fistula repair body, which is then implanted into the fistula tract, this design does not tightly fix adjacent layers together, leaving gaps between them. This allows pus, inflammatory exudate, bloody secretions, and other substances to drain out of the fistula tract through these gaps, facilitating fistula repair and healing.
[0010] Based on this, the technical solution of the present invention is as follows:
[0011] In a first aspect, the present invention provides an anal fistula repair component, comprising a first sheet and a second sheet, each independently formed; both the first sheet and the second sheet are prepared from biodegradable materials.
[0012] The first layer is a porous structure with a thickness of 0.1-0.5 mm, a pore size range of 1-350 μm, a porosity of 10-20%, and a degradation time of 12-26 weeks postoperatively; the second layer is a porous structure with a thickness of 0.05-0.2 mm, a pore size range of 50-350 μm, a porosity of 20-35%, and a degradation time of 4-12 weeks postoperatively.
[0013] The first layer plays a crucial role in providing mechanical strength support during anal fistula repair. It needs to maintain the necessary mechanical strength for 3-6 months post-surgery, with degradation occurring between weeks 12 and 26 post-surgery, ideally completed between weeks 22 and 26. The second layer contacts the fistula repair tissue before the first. Its porous structure (50-350 μm pore size) and high porosity (20-35%) facilitate cell attachment and rapid proliferation, promoting new tissue formation. The second layer also provides some mechanical support. After the second layer degrades between weeks 4 and 12 post-surgery, the porous structure of the first layer (1-350 μm pore size) and its 10-20% porosity also promote tissue growth and fistula repair.
[0014] Preferably, the anal fistula repair component of the present invention further includes a third layer, which is also made of a biodegradable material. This third layer is a porous structure with a thickness of 0.05-0.1 mm, a pore size ranging from 1-200 μm, a porosity of 30-45%, and a degradation time of 2-4 weeks post-surgery. Simultaneously, this third layer carries antibiotics.
[0015] Therefore, in a preferred embodiment of the present invention, the anal fistula repair component consists of a first layer, a second layer, and a third layer, each independently formed; wherein the third layer is loaded with antibiotics and serves as the outer layer; the second layer and the first layer may not be loaded with drugs or preparations and serve as the middle layer and the inner layer, respectively. Before use, it is rolled into a nested tubular or conical shape.
[0016] Further optimization involves the first layer carrying a regeneration and repair regulator to promote cell proliferation and accelerate the healing of anal fistula wounds; and the second layer carrying an immunomodulator to inhibit inflammatory responses, regulate immune responses, and promote the healing of anal fistula wounds.
[0017] Among them, the regeneration and repair regulator is selected from any one or more combinations of thymopentin, basic fibroblast growth factor, epidermal growth factor, vascular endothelial growth factor, concentrated growth factor, transforming growth factor-β1 or mesenchymal stem cells.
[0018] The immunomodulatory agent is selected from any one or more combinations of infliximab, adalimumab, ustekinumab, vedolizumab, sertozumab, methotrexate, azathioprine, or 6-mercaptopurine.
[0019] The antibiotic is selected from any one or more combinations of ciprofloxacin, metronidazole, gentamicin, erythromycin, mupirocin, or levofloxacin.
[0020] Therefore, in another preferred embodiment of the present invention, the anal fistula repair component is composed of a first layer, a second layer, and a third layer, each independently formed; wherein the third layer is loaded with antibiotics as the outer layer; the second layer carries an immunomodulator as the middle layer; and the first layer carries a regeneration and repair regulator as the inner layer. Before use, it is rolled into a nested tubular or conical shape.
[0021] Based on the recovery cycle of anal fistula, the three layers degrade in stages from the outside in, simultaneously releasing corresponding drugs or preparations to achieve therapeutic effects. Specifically:
[0022] The outer layer corresponds to the acute phase, i.e., the postoperative local inflammatory response phase. During the acute phase, it is necessary to quickly control the infection and alleviate symptoms. Placing antibiotics in the outermost layer allows for rapid release, which can control acute attacks of anal fistulas caused by bacterial infection and prevent the spread of secondary infection to surrounding tissues.
[0023] The middle layer corresponds to the remission period, requiring the maintenance of disease stability and prevention of relapse. Immunomodulators are placed in the middle layer, and the outermost layer is completely degraded. As the middle layer gradually degrades, the immunomodulators are released, which helps to reduce inflammation and promote and maintain fistula healing.
[0024] The inner layer corresponds to the consolidation period, which requires repair of the perianal microenvironment. The regenerative repair regulator is placed in the inner layer, and as the middle layer degrades completely, the regenerative repair regulator is released, repairing and consolidating the perianal microenvironment.
[0025] In terms of materials, all three layers are made from biodegradable materials, including any one or more copolymers or combinations of biodegradable polyurethane, polylactic acid, polyglycolic acid, polycaprolactone, polyethylene glycol, polyvinyl alcohol, polycarbonate, polyhydroxyalkanoates, PHB / PHV copolymers, polyanhydrides, polydioxanone, and bacterial cellulose.
[0026] Preferably, the biodegradable material used to make the first layer is selected from any one or more copolymers or combinations thereof from the group consisting of: biodegradable polyurethane with a weight-average molecular weight of 50k-280kDa, polylactic acid with a weight-average molecular weight of 50k-200kDa, polyglycolic acid with a weight-average molecular weight of 50k-200kDa, polycaprolactone with a weight-average molecular weight of 40k-200kDa, polyethylene glycol with a weight-average molecular weight of 20k-80kDa, polyvinyl alcohol with a weight-average molecular weight of 30k-100kDa, polycarbonate with a weight-average molecular weight of 40k-120kDa, polyhydroxyalkanoates with a weight-average molecular weight of 100k-200kDa, PHB / PHV copolymers with a weight-average molecular weight of 120k-250kDa, polyanhydrides with a weight-average molecular weight of 20k-50kDa, polydioxanone with a weight-average molecular weight of 80k-300kDa, and poly(p-dioxanone) with a weight-average molecular weight of 300k-800kDa. Bacterial cellulose, a copolymer of polycaprolactone and polyethylene glycol with a weight-average molecular weight of 50k-280kDa.
[0027] Preferably, the biodegradable material used to make the second layer is selected from any one or more copolymers or combinations of the following: biodegradable polyurethane with a weight-average molecular weight of 20k-80kDa, polylactic acid with a weight-average molecular weight of 15k-80kDa, polyglycolic acid with a weight-average molecular weight of 20k-80kDa, polycaprolactone with a weight-average molecular weight of 15k-50kDa, polyethylene glycol with a weight-average molecular weight of 10k-25kDa, polyvinyl alcohol with a weight-average molecular weight of 15k-50kDa, polycarbonate with a weight-average molecular weight of 15k-50kDa, polyhydroxyalkanoates with a weight-average molecular weight of 40k-120kDa, PHB / PHV copolymers with a weight-average molecular weight of 40k-150kDa, polyanhydrides with a weight-average molecular weight of 15k-30kDa, poly(p-dioxanone) with a weight-average molecular weight of 20k-60kDa, and poly(p-dioxanone) with a weight-average molecular weight of 100k-300kDa. Bacterial cellulose with a weight average molecular weight of 20k-80kDa, and a copolymer of polycaprolactone and polyethylene glycol with a weight average molecular weight of 20k-80kDa.
[0028] Preferably, the biodegradable material used to make the third layer is selected from any one or more copolymers or combinations of the following: biodegradable polyurethane with a weight-average molecular weight of 8k-30kDa, polylactic acid with a weight-average molecular weight of 8k-20kDa, polyglycolic acid with a weight-average molecular weight of 8k-30kDa, polycaprolactone with a weight-average molecular weight of 5k-20kDa, polyethylene glycol with a weight-average molecular weight of 8k-15kDa, polyvinyl alcohol with a weight-average molecular weight of 5k-20kDa, and so on. Polycarbonate with a molecular weight of 5k-20kDa, polyhydroxyalkanoate with a weight average molecular weight of 8k-25kDa, PHB / PHV copolymer with a weight average molecular weight of 10k-50kDa, polyanhydride with a weight average molecular weight of 8k-20kDa, polydioxanone with a weight average molecular weight of 10k-25kDa, bacterial cellulose with a weight average molecular weight of 40k-150kDa, and polycaprolactone-polyethylene glycol copolymer with a weight average molecular weight of 8k-30kDa.
[0029] In a second aspect, the present invention provides a method for preparing the above-mentioned anal fistula repair component. A first layer, a second layer, and a third layer are fabricated separately. The fabrication method includes the following steps:
[0030] (a) Dissolve the biodegradable material in a solvent, add a pore-forming agent, and obtain a biodegradable material solution;
[0031] (b) The first layer, the second layer, or the third layer are produced by electrospinning or casting.
[0032] (c) Post-treatment: remove solvent and dry.
[0033] Preferably, when making the first layer, the pore-forming agent has a particle size of 1-350 μm, and the biodegradable material solution is composed of the following components by mass percentage: 10-30% biodegradable material and 5-10% pore-forming agent, with the remainder being solvent;
[0034] Preferably, when making the second layer, the pore-forming agent has a particle size of 50-350 μm, and the biodegradable material solution is composed of the following components by mass percentage: 10-30% biodegradable material and 10-15% pore-forming agent, with the remainder being solvent;
[0035] Preferably, when making the third layer, the pore-forming agent has a particle size of 1-200 μm, and the biodegradable material solution is composed of the following components by mass percentage: 10-30% biodegradable material and 15-20% pore-forming agent, with the remainder being solvent.
[0036] The pore-forming agent is selected from at least one of sodium chloride, sucrose, gelatin balls, monosodium glutamate, modified cellulose, urea, polyethylene glycol, and polyvinylpyrrolidone, preferably NaCl.
[0037] Preferably, the post-processing steps include:
[0038] (1) Removal of solvent and moisture: freeze-dry the first, second or third layer of the above-mentioned anal fistula repair component to remove solvent residue and moisture residue, so that the total amount of solvent residue in the anal fistula repair component is ≤0.1% and the moisture residue is ≤0.5%;
[0039] (2) Remove the rough edges or uneven thickness of the first, second or third layer of the dried anal fistula repair component, confirm that there are no bubbles, no damage, no foreign matter, and that the thickness is uniform, cut it to the required size, and sterilize it by irradiation and package it.
[0040] Further optimization involves loading regenerative repair modulators, immunomodulators, and antibiotics onto the corresponding sheets via impregnation or spraying. Loading can be performed separately on each sheet during preparation, or it can be done when the sheets are wrapped in the surgical roll.
[0041] A third aspect of the present invention provides a method for using the aforementioned anal fistula repair component, comprising the following steps:
[0042] (1) Wrap the first layer one or more times to form a columnar or conical inner layer;
[0043] (2) The second layer is attached to the outside of the inner layer and rolled up one or more times to form a columnar or conical outer layer. The columnar or conical body formed by the first layer and the second layer in sequence is the absorbable anal fistula repair body. The absorbable anal fistula repair body is used for implantation into the fistula tract.
[0044] Preferably, a third layer is rolled up in addition to the outer layer. Specifically, the third layer is attached to the outer layer and rolled up one or more times to form a columnar or conical outermost layer.
[0045] Further preferably, when each layer is wound, the drug or formulation is loaded according to the method described in the second aspect. It is worth noting that when the first layer is wound, a regeneration and repair modifier is sprayed on the surface of the first layer (i.e., the side facing the second layer); when the second layer is wound, an immunomodulator is sprayed on the surface of the second layer (i.e., the side facing the third layer); and an antibiotic is sprayed on the surface of the third layer, i.e., the side away from the second layer.
[0046] In a fourth aspect, the present invention provides an anal fistula repair material, which is an absorbable anal fistula repair body obtained according to the method of use described in the third aspect above.
[0047] In a fifth aspect, this invention provides the application of the aforementioned anal fistula repair component or material in the preparation of devices and drugs for treating anal fistulas. The products of this invention can be used individually or in combination with other devices for anal fistula repair as a complete product.
[0048] The beneficial protections and effects of this invention are as follows:
[0049] (1) The anal fistula repair product of this invention uses biodegradable materials that are gradually absorbed by the human body, avoiding long-term foreign body residue and greatly reducing the risk of chronic inflammation or infection that may be caused by traditional non-degradable materials. In addition, this patented product is made of non-animal-derived materials, has good biocompatibility, and is non-immunogenic.
[0050] (2) In terms of mechanical properties and elasticity, the anal fistula repair component of the present invention can provide sufficient mechanical support required during the anal fistula repair process. The first layer, as the main supporting layer, provides continuous and sufficient mechanical support during the anal fistula healing period to ensure that the anal fistula is repaired before the patch support strength decreases. The maximum tensile force of the first layer reaches 26.34 N or more, the elastic modulus reaches 284.29 MPa or more, and the elongation at break reaches 493.25% or more, which can meet the mechanical support strength required during the anal fistula repair process. The maximum tensile force of the absorbable anal fistula repair body in use reaches 39.27 N or more, the elastic modulus reaches 340.32 MPa or more, and the elongation at break reaches 897.91% or more, which can well meet the mechanical performance requirements of the absorbable anal fistula repair body during the anal fistula repair process. At the same time, the absorbable anal fistula repair body prepared by the present invention has an elastic modulus of 340.32 MPa, is soft and elastic, which can greatly reduce tissue damage during implantation, reduce patient discomfort, and improve patient acceptance.
[0051] (3) The anal fistula repair component prepared in this invention undergoes phased degradation of each layer. When the three layers carry the drug and degrade in layers, the third layer carries the antibiotic and degrades completely in 2-4 weeks, the second layer degrades completely in 4-12 weeks, and the first layer degrades completely in 16-26 weeks. In the acute phase 2-4 weeks after surgery, the antibiotics in the third layer, which is the outermost layer, are released, playing an effective antibacterial and anti-inflammatory role and greatly reducing the risk of infection. 4-12 weeks after surgery, the outermost layer has completely degraded, and the immunomodulators in the second layer, which is the middle layer, are released, promoting fistula healing. 12-26 weeks after surgery, the middle layer has completely degraded, and the first layer, which is the innermost layer, gradually degrades. The concentration of the regeneration and repair regulators released into the fistula in the inner layer increases, further facilitating fistula healing. This invention overcomes the shortcomings of long treatment cycles and slow efficacy of drugs, and avoids the very cumbersome operation steps of daily cleaning, dressing changes, debridement, and disinfection after surgery, which helps to improve the patient's quality of life and physical and mental health.
[0052] (4) The porous structure of each layer of the anal fistula repair component prepared by the present invention facilitates the flow of nutrients required for tissue regeneration and promotes tissue growth and repair. The pore size and porosity in the second layer facilitate cell attachment and growth, promote cell proliferation, and contribute to the repair of anal fistula.
[0053] (5) In addition to providing the main mechanical support, the first layer can also drain pus, inflammatory exudate, bloody secretions and other substances to the outside of the fistula.
[0054] (6) When the fistula repair component of the present invention is used, the first layer is the inner layer, the second layer is the middle layer, and the third layer is the outermost layer. The first layer is first rolled up several times, and the second layer is attached to the outside of the inner layer and rolled up one or more times to restrict the contact of the first layer. The third layer is attached to the outside of the second layer and rolled up one or more times to restrict the contact of the second layer. The contact restriction of the three layers not only effectively maintains the shape after rolling, but also forms a certain gap between different layers, which will not hinder the release of drugs. Purulent, inflammatory exudate, bloody secretions and other substances can be drained to the outside of the fistula through the above gaps.
[0055] (7) The anal fistula repair component of the present invention can be rolled into absorbable anal fistula repair bodies of appropriate size, shape and number and implanted into the fistula tract by the doctor according to the specific situation of the patient's fistula tract thickness, number and direction during surgery; and whether to load drugs or preparations, and the type and dosage of drugs or preparations loaded, according to the patient's drug allergy history. Attached Figure Description
[0056] Figure 1 This is a diagram illustrating the first, second, and third layers of the anal fistula repair assembly provided in Embodiment 3 of the present invention.
[0057] Figure 2 This is an illustration of an absorbable anal fistula repair body formed by rolling up the layers of the anal fistula repair component provided in Embodiment 7 of the present invention. Detailed Implementation
[0058] The following embodiments and experimental examples further illustrate the present invention and should not be construed as limiting the invention. The embodiments do not include a detailed description of conventional methods, which are well known to those skilled in the art and described in numerous publications.
[0059] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as are familiar to those skilled in the art. Furthermore, any methods and materials similar to or equivalent to those described herein may be applied to this invention, and the preferred embodiments and materials described in the specific implementation are for illustrative purposes only.
[0060] According to one aspect of the present invention, an anal fistula repair component is provided, comprising a first sheet and a second sheet, each independently formed, wherein the first sheet and the second sheet are prepared from a biodegradable material.
[0061] The first sheet is a porous structure layer with a thickness of 0.1-0.5 mm, a pore size range of 1-350 μm, a porosity of 10-20%, and a degradation time of 12-26 weeks after surgery; the second sheet is a porous structure layer with a thickness of 0.05-0.2 mm, a pore size range of 50-350 μm, a porosity of 20-35%, and a degradation time of 4-12 weeks after surgery.
[0062] The anal fistula repair component provided by the present invention includes at least a first sheet and a second sheet, each of which is independently formed.
[0063] During anal fistula repair, if the biodegradable repair material or catheter degrades too quickly, it may lose its support and drainage function before the fistula tract is fully healed, leading to repair failure. If it degrades too slowly, it prolongs the time the foreign body remains in the body, increasing the risk of infection and the body's foreign body reaction. Anal fistula treatment typically results in improvement within 3-6 months. In this patented anal fistula repair component, the first layer degrades between the 12th and 26th week post-surgery. This ensures the component does not degrade too quickly, preventing premature softening and fistula collapse, maintaining the necessary mechanical support during repair, providing drainage, and preventing prolonged retention in the body.
[0064] The first layer provides the main mechanical strength support for fistula repair and needs to maintain the required mechanical strength for 3-6 months post-surgery. Its degradation occurs between week 12 and week 26 post-surgery, preferably week 22-26. The degradation time of the first layer can be, but is not limited to, week 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, and 26. The thickness of the first layer can be, but is not limited to, 0.1 mm, 0.2 mm, 0.3 mm, 0.4 mm, and 0.5 mm.
[0065] In the process of anal fistula repair, the first and second layers together constitute a columnar or conical absorbable fistula repair body. The first layer is rolled up one or more times to form a columnar or conical inner layer; the second layer is also rolled up one or more times, forming a columnar or conical shape, located outside the inner layer. Besides providing primary mechanical support, the first layer also drains pus, inflammatory exudate, and bloody secretions to the outside of the fistula tract. The second layer contacts the fistula repair tissue before the first layer. Its porous structure (50-350 μm pore size) and porosity of up to 20-35% facilitate the attachment and rapid proliferation of repair cells, promoting granulation tissue formation. The second layer also provides some mechanical support. As the second layer gradually degrades from week 4 to week 12 post-surgery, the porous structure of the first layer (1-350 μm pore size) and its 10-20% porosity also promote tissue growth and fistula repair.
[0066] The degradation time of the second layer can be, but is not limited to, week 4, week 5, week 6, week 7, week 8, week 9, week 10, week 11, and week 12.
[0067] The thickness of the second layer can be, but is not limited to, 0.05mm, 0.08mm, 0.1mm, 0.12mm, 0.14mm, 0.16mm, 0.18mm, or 0.2mm.
[0068] The pore size range of the first layer may be, but is not limited to, 1μm, 3μm, 5μm, 10μm, 15μm, 20μm, 25μm, 50μm, 75μm, 100μm, 2μm, 125μm, 175μm, 200μm, 225μm, 250μm, 275μm, 300μm, 325μm, and 350μm.
[0069] The porosity of the first layer can be, but is not limited to, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, or 20%.
[0070] The pore size range of the second layer can be, but is not limited to, 50μm, 75μm, 100μm, 2μm, 125μm, 175μm, 200μm, 225μm, 250μm, 275μm, 300μm, 325μm, and 350μm.
[0071] The porosity of the second layer can be, but is not limited to, 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, 30%, 31%, 32%, 33%, 34%, or 35%.
[0072] In a preferred embodiment of the present invention, the anal fistula repair component further includes a third layer, which is prepared from a biodegradable material. The third layer is a porous structure with a thickness of 0.05-0.1 mm, a pore size ranging from 1-200 μm, a porosity of 30-45%, and a degradation time of 2-4 weeks postoperatively. The third layer carries antibiotics.
[0073] In the preferred embodiment described above, the anal fistula repair component includes a first layer, a second layer, and a third layer. When these three layers are used, they together constitute a columnar or conical absorbable anal fistula repair body. Specifically, the first layer is wound one or more times to form a columnar or conical inner layer; the second layer is wound one or more times to form a columnar or conical middle layer located outside the inner layer; and the third layer is wound one or more times to form a columnar or conical outermost layer located outside the outer layer. The outermost layer (formed by the winding of the third layer) carries an antibiotic, selected from any one or more combinations of ciprofloxacin, metronidazole, gentamicin, erythromycin, mupirocin, or levofloxacin. The antibiotic can be added during the production of the third layer, or the doctor can select the specific antibiotic based on the patient's symptoms, drug allergy history, etc., and add the antibiotic when using the third layer. The third layer, carrying antibiotics, provides effective antibacterial and anti-inflammatory effects on the fistula, helping patients overcome the postoperative local inflammatory response period. The porous structure of the third layer, with a pore size range of 1-200μm and a porosity of 30-45%, also facilitates the loading of antibiotics into the layer.
[0074] The degradation time of the third layer can be, but is not limited to, week 2, week 3, and week 4.
[0075] The thickness of the third layer can be, but is not limited to, 0.05mm, 0.06mm, 0.07mm, 0.08mm, 0.09mm, or 0.1mm.
[0076] The pore size range of the third layer can be, but is not limited to, 1μm, 5μm, 10μm, 20μm, 50μm, 75μm, 100μm, 125μm, 150μm, 175μm, and 200μm.
[0077] The porosity of the third layer can be, but is not limited to, 30%, 31%, 32%, 33%, 34%, 35%, 36%, 37%, 38%, 39%, 40%, 41%, 42%, 43%, 44%, and 45%.
[0078] The porous structure of the first and second layers, combined with their porosity, provides attachment points and growth space for cell attachment, proliferation, and tissue growth, which is beneficial for the repair of anal fistulas.
[0079] In a preferred embodiment of the present invention, the first sheet carries a regeneration and repair modulator, and the second sheet carries an immunomodulator.
[0080] The regeneration and repair regulator is selected from any one or more combinations of thymopentin, basic fibroblast growth factor, epidermal growth factor, vascular endothelial growth factor, concentrated growth factor, transforming growth factor-β1, or mesenchymal stem cells.
[0081] The immunomodulatory agent is selected from any one or more combinations of infliximab, adalimumab, ustekinumab, vedolizumab, sertozumab, methotrexate, azathioprine, or 6-mercaptopurine.
[0082] In the above preferred embodiments, the regenerative repair modifier and the immune modifier can be added to the first layer and the second layer during production, or the doctor can select them specifically according to the patient's condition and add them when using the anal fistula repair component.
[0083] The first layer carries a regeneration and repair regulator to further promote cell proliferation, tissue repair and regeneration, and accelerate the healing of anal fistula wounds. Specifically, the regeneration and repair regulator can be any one or a combination of thymopentin, basic fibroblast growth factor, epidermal growth factor, vascular endothelial growth factor, concentrated growth factor, transforming growth factor-β1, or mesenchymal stem cells. Its mechanism of action is as follows:
[0084] Thymopentin (TP5) is an immunomodulator that promotes the differentiation, maturation, and activation of T lymphocytes, increases the number and activity of T lymphocytes, activates helper T lymphocytes to produce various cytokines, and regulates the function of the immune system. Simultaneously, TP5 can also enhance the activity of natural killer (NK) cells and improve the phagocytic function of macrophages, thereby strengthening the body's immune defense capabilities.
[0085] Basic fibroblast growth factor (bFGF) accelerates wound healing through mechanisms such as promoting cell proliferation, differentiation, and angiogenesis.
[0086] Epidermal growth factor (EGF) can bind to EGF receptors on the cell surface, activate the downstream MEK / ERK signaling pathway, promote cell proliferation, migration and differentiation, and thus accelerate wound healing.
[0087] Vascular endothelial growth factor (VEGF) primarily promotes angiogenesis. By binding to receptors on vascular endothelial cells, it increases vascular permeability, stimulates vascular endothelial cell proliferation and migration, forms new blood vessels, improves local oxygen and nutrient supply to the wound, and promotes wound healing.
[0088] Concentrated growth factor (CGF) is rich in various growth factors, such as EGF, PDGF, VEGF, IGF-1R, TGF-β1, and Ang-II, which can promote the division, proliferation, and migration of fibroblasts and endothelial cells. Simultaneously, CGF also possesses anti-inflammatory properties, reducing the secretion of inflammatory factors, regulating immune responses, and promoting wound healing.
[0089] Transforming growth factor-β1 (TGF-β1) reduces inflammation by inhibiting Th1 and Th17 cell differentiation and decreasing the production of pro-inflammatory cytokines, thus creating a favorable local environment for fistula healing. TGF-β1 stimulates fibroblast proliferation and collagen synthesis, promoting granulation tissue growth and wound closure, accelerating fistula healing. During the proliferative phase of wound healing, TGF-β1 promotes extracellular matrix synthesis, enhances tissue repair capacity, and contributes to the repair and regeneration of normal tissue surrounding the fistula.
[0090] Mesenchymal stem cells (MSCs) have immunomodulatory and anti-inflammatory effects, can differentiate into various cell types, secrete a variety of growth factors, promote tissue repair and regeneration, and have development potential for Crohn's disease-related anal fistulas.
[0091] It should be noted that concentrated growth factor (CGF) can be prepared by a professional doctor by collecting the patient's own blood.
[0092] Equipment preparation: Specific centrifuge equipment (such as Medifuge MF200 or specific CGF equipment).
[0093] Blood collection: Collect autologous venous blood (usually 8 mL-20 mL).
[0094] Centrifugation procedure: After loading the blood sample into the centrifuge tube, centrifuge according to the specific centrifugation procedure. The specific procedure may vary depending on the equipment and laboratory requirements. Common procedures include accelerating for 30 seconds, centrifuging at 2700 rpm for 2 minutes, centrifuging at 2400 rpm for 4 minutes, centrifuging again at 2700 rpm for 4 minutes, and finally centrifuging at 3000 rpm for 3 minutes.
[0095] CGF isolation: After centrifugation, the blood will separate into three layers, with the middle layer being the concentrated growth factor.
[0096] The second layer carries immunomodulators to suppress inflammatory responses and regulate immune responses. These immunomodulators can be any one or a combination of infliximab, adalimumab, ustekinumab, vedocilzumab, certolizumab Pegol, methotrexate, azathioprine, or 6-mercaptopurine. Infliximab is a currently approved biologic for Crohn's disease-related anal fistulas, reducing the number of pfCD or abdominal fistulas and promoting and maintaining fistula healing. Studies have shown that adalimumab, ustekinumab, vedocilzumab, certolizumab Pegol, methotrexate, azathioprine, or 6-mercaptopurine are effective in treating Crohn's disease-related anal fistulas. Their mechanisms of action are as follows:
[0097] Infliximab (IFX) is a monoclonal antibody against tumor necrosis factor (TNF-α). By specifically binding to TNF-α, it blocks its interaction with the tumor necrosis factor (TNF) receptor, inhibits the inflammatory effect of TNF, and thus reduces the inflammatory response associated with anal fistula.
[0098] Adalimumab: Specifically binds to TNF-α, blocking its interaction with cell surface receptors and inhibiting the inflammatory response.
[0099] Ustekinumab is an anti-IL-12 / 23 monoclonal antibody that can inhibit the activity of IL-12 and IL-23, thereby reducing the inflammatory response and showing some efficacy in Crohn's disease-associated anal fistula.
[0100] Vedolizumab is an anti-integrin monoclonal antibody that can block the interaction between integrins and ligands, regulate the adhesion and migration of immune cells, thereby inhibiting the inflammatory response and showing some efficacy against Crohn's disease-related anal fistula.
[0101] Certolizumab Pegol: Specifically binds to TNF-α, inhibits its activity, and reduces inflammation.
[0102] Methotrexate is a folic acid antagonist that inhibits DNA synthesis by interfering with folic acid metabolism, thereby suppressing the proliferation of immune cells and regulating immune responses. It can be used to treat Crohn's disease-related anal fistulas.
[0103] Azathioprine can inhibit purine synthesis, thereby inhibiting the proliferation of immune cells and regulating immune responses. It is often used to treat Crohn's disease-related anal fistulas, and can lead to partial or complete healing of the fistulas in some patients.
[0104] 6-Mercaptopurine has a similar mechanism of action to azathioprine, inhibiting the proliferation of immune cells and regulating immune function, and has a certain therapeutic effect on Crohn's disease-related anal fistula.
[0105] In the preferred embodiment described above, the first layer carries a regeneration and repair regulator, the second layer carries an immunomodulator, and the third layer carries an antibiotic. The first layer is located on the inner layer, the second layer on the outer layer, and the third layer on the outermost layer. During fistula repair, the antibiotic in the third layer effectively combats inflammation and bacteria in the fistula, helping the patient overcome the postoperative local inflammatory response period. The immunomodulator in the second layer rapidly inhibits the inflammatory response, regulates the immune response, and reduces tissue damage around the fistula. The regeneration and repair regulator in the first layer promotes cell proliferation, tissue repair, and regeneration. This synergistic effect can improve treatment efficacy, accelerate the fistula healing process, and potentially reduce the recurrence rate. The degradation time of each layer differs postoperatively. During the postoperative local inflammatory response period, it is necessary to quickly control infection and alleviate symptoms. Antibiotics can control the inflammatory response caused by bacterial infection and prevent the spread of secondary infection to surrounding tissues. Placing the antibiotic in the third layer (i.e., the outermost layer of the fistula repair body) allows for rapid release to inhibit bacteria. During the 2nd to 4th week post-surgery, the local inflammatory response is controlled. At this time, the third layer (the outermost layer of the fistula repair) degrades as the tissue gradually repairs, avoiding pressure or damage to the newly formed tissue. The porous structure and pore space of the second layer (the outermost layer of the fistula repair) facilitate cell attachment, proliferation, and tissue repair. During the gradual degradation of the second layer, its immunomodulators are also gradually released, further inhibiting the inflammatory response. From the 4th to the 12th week post-surgery, the second layer (the outermost layer of the fistula repair) has completed its degradation, and new tissue continues to grow, filling the spaces previously occupied by the third and second layers. During cell proliferation and tissue repair, the first layer (the innermost layer of the fistula repair) provides sufficient mechanical support, and its regenerative repair regulators are gradually and slowly released, further facilitating tissue growth and fistula repair. By the 12th to 26th week after surgery, when the new tissue in the anal fistula has basically grown, the first layer (i.e. the inner layer of the anal fistula repair) gradually degrades until it is completely degraded.
[0106] In a preferred embodiment of the present invention, the biodegradable material includes any one or more copolymers or combinations of biodegradable polyurethane, polylactic acid, polyglycolic acid, polycaprolactone, polyethylene glycol, polyvinyl alcohol, polycarbonate, polyhydroxyalkanoates, PHB / PHV copolymers, polyanhydrides, polydioxanone, and bacterial cellulose.
[0107] In the preferred embodiments described above, the biodegradable material may be any one or a combination of biodegradable polyurethane (PUR), polylactic acid (PLA), polyglycolic acid (PGA, also known as polyhydroxyacetic acid), polycaprolactone (PCL), polyethylene glycol (PEG), polyvinyl alcohol (PVA), polycarbonate (PPC), polyhydroxy fatty acid ester (PHA), polyhydroxybutyrate-hydroxyvalerate copolymer (PHB / PHV copolymer), polyanhydride, polydioxanone (PDO), and bacterial cellulose, or copolymers of multiple of these materials, such as polycaprolactone (PCL)-polyethylene glycol (PEG) copolymer and polylactic acid (PLA)-polyglycolic acid (PGA) copolymer.
[0108] In a further preferred embodiment, the biodegradable material used to make the first sheet is preferably a copolymer or combination of any one or more of the following groups: biodegradable polyurethane with a weight-average molecular weight of 50k-280kDa, polylactic acid with a weight-average molecular weight of 50k-200kDa, polyglycolic acid with a weight-average molecular weight of 50k-200kDa, polycaprolactone with a weight-average molecular weight of 40k-200kDa, polyethylene glycol with a weight-average molecular weight of 20k-80kDa, polyvinyl alcohol with a weight-average molecular weight of 30k-100kDa, polycarbonate with a weight-average molecular weight of 40k-120kDa, polyhydroxyalkanoates with a weight-average molecular weight of 100k-200kDa, PHB / PHV copolymer with a weight-average molecular weight of 120k-250kDa, and a biodegradable polyhydroxyalkanoate with a weight-average molecular weight of 20kDa. Polyanhydride with a weight average molecular weight of -50kDa, polydioxanone with a weight average molecular weight of 80k-300kDa, bacterial cellulose with a weight average molecular weight of 300k-800kDa, and polycaprolactone-polyethylene glycol copolymer with a weight average molecular weight of 50k-280kDa.
[0109] The biodegradable material used to fabricate the second layer is preferably selected from any one or more copolymers or combinations thereof from the group consisting of: biodegradable polyurethane with a weight-average molecular weight of 20k-80kDa, polylactic acid with a weight-average molecular weight of 15k-80kDa, polyglycolic acid with a weight-average molecular weight of 20k-80kDa, polycaprolactone with a weight-average molecular weight of 15k-50kDa, polyethylene glycol with a weight-average molecular weight of 10k-25kDa, polyvinyl alcohol with a weight-average molecular weight of 15k-50kDa, polycarbonate with a weight-average molecular weight of 15k-50kDa, polyhydroxyalkanoates with a weight-average molecular weight of 40k-120kDa, PHB / PHV copolymers with a weight-average molecular weight of 40k-150kDa, polyanhydrides with a weight-average molecular weight of 15k-30kDa, polydioxanone with a weight-average molecular weight of 20k-60kDa, and other biodegradable materials with a weight-average molecular weight of 100k-300kDa. Bacterial cellulose with a weight average molecular weight of 20k-80kDa, and a copolymer of polycaprolactone and polyethylene glycol with a weight average molecular weight of 20k-80kDa.
[0110] The biodegradable material used to fabricate the third layer is preferably a copolymer or combination of any one or more of the following groups: biodegradable polyurethane with a weight-average molecular weight of 8k-30kDa, polylactic acid with a weight-average molecular weight of 8k-20kDa, polyglycolic acid with a weight-average molecular weight of 8k-30kDa, polycaprolactone with a weight-average molecular weight of 5k-20kDa, polyethylene glycol with a weight-average molecular weight of 8k-15kDa, polyvinyl alcohol with a weight-average molecular weight of 5k-20kDa, and other biodegradable materials. The composition includes polycarbonate with a weight average molecular weight of 5k-20kDa, polyhydroxy fatty acid ester with a weight average molecular weight of 8k-25kDa, PHB / PHV copolymer with a weight average molecular weight of 10k-50kDa, polyanhydride with a weight average molecular weight of 8k-20kDa, polydioxanone with a weight average molecular weight of 10k-25kDa, bacterial cellulose with a weight average molecular weight of 40k-150kDa, and polycaprolactone-polyethylene glycol copolymer with a weight average molecular weight of 8k-30kDa.
[0111] In a further preferred embodiment, the biodegradable material is a biodegradable polyurethane (PUR) or a copolymer of polycaprolactone (PCL) and polyethylene glycol (PEG).
[0112] Biodegradable polyurethane (PUR) can be purchased commercially or prepared by referring to the preparation method in the embodiment of patent 201811568720.2.
[0113] The copolymer of polycaprolactone (PCL) and polyethylene glycol (PEG) can be purchased commercially or prepared by referring to the preparation method in the example of patent 202111122492.8.
[0114] According to another aspect of the present invention, a method for preparing an anal fistula repair component is provided, wherein a first layer, a second layer, and a third layer are respectively fabricated.
[0115] The production method includes the following steps:
[0116] (a) Dissolve the biodegradable material in a solvent, add a pore-forming agent, and obtain a biodegradable material solution;
[0117] (b) The first layer, the second layer, or the third layer are produced by electrospinning or casting.
[0118] (c) Remove solvent and dry.
[0119] Preferably, when making the first layer, the pore-forming agent has a particle size of 1-350 μm, and the biodegradable material solution is composed of the following components by mass percentage: 10-30% biodegradable material and 5-10% pore-forming agent, with the remainder being solvent;
[0120] Preferably, when making the second layer, the pore-forming agent has a particle size of 50-350 μm, and the biodegradable material solution is composed of the following components by mass percentage: 10-30% biodegradable material and 10-15% pore-forming agent, with the remainder being solvent;
[0121] Preferably, when making the third layer, the pore-forming agent has a particle size of 1-200 μm, and the biodegradable material solution is composed of the following components by mass percentage: 10-30% biodegradable material and 15-20% pore-forming agent, with the remainder being solvent.
[0122] The present invention provides a method for preparing an anal fistula repair component. The method involves fabricating multiple sheets of biodegradable material using electrospinning or casting. Pores in each sheet are created using a pore-forming agent. A suitable solvent is selected based on the chosen biodegradable material to prepare the biodegradable material solution, such as one or more of tetrahydrofuran (THF), dichloroethane, dimethyl ether, or N,N-dimethylformamide. Specifically, the pore-forming agent is added to the biodegradable material solution. The pore-forming agent is insoluble in the solution. After the sheets are formed, the pore-forming agent is removed during solvent removal, resulting in pores of the pore size. Of course, the solvent removal process removes not only the pore-forming agent but also the solvent that dissolves the biodegradable material. The particle size range of the porogen used in fabricating the first layer is 1-350 μm, specifically, but not limited to, 1 μm, 5 μm, 10 μm, 25 μm, 50 μm, 75 μm, 100 μm, 125 μm, 150 μm, 175 μm, 200 μm, 225 μm, 250 μm, 275 μm, 300 μm, 325 μm, and 350 μm. The particle size range of the porogen used in fabricating the second layer is 50-350 μm, specifically, but not limited to, 50 μm, 75 μm, 100 μm, 125 μm, 150 μm, 175 μm, 200 μm, 225 μm, 250 μm, 275 μm, 300 μm, 325 μm, and 350 μm. The particle size range of the porogen used in the fabrication of the third layer is 1-200 μm, specifically, but not limited to, 1 μm, 5 μm, 10 μm, 15 μm, 20 μm, 25 μm, 50 μm, 75 μm, 100 μm, 125 μm, 150 μm, 175 μm, and 200 μm.
[0123] To achieve a certain porosity within the layers, the mass percentage of the porogen in the biodegradable material solution needs to reach a corresponding range. When fabricating the first layer, the biodegradable material solution, by mass percentage, comprises 10-30% biodegradable material, specifically, but not limited to, 10%, 12%, 14%, 16%, 18%, 20%, 22%, 24%, 26%, 28%, and 30%; and 5-10% porogen, specifically, but not limited to, 5%, 6%, 7%, 8%, 9%, and 10%. When fabricating the second layer, the biodegradable material solution, by mass percentage, comprises 10-30% biodegradable material, specifically, but not limited to, 10%, 12%, 14%, 16%, 18%, 20%, 22%, 24%, 26%, 28%, and 30%; and a porogen, comprising 10-15%, specifically, but not limited to, 10%, 11%, 12%, 13%, 14%, and 15%. When fabricating the third layer, the biodegradable material solution, by mass percentage, comprises 10-30% biodegradable material, specifically, but not limited to, 10%, 12%, 14%, 16%, 18%, 20%, 22%, 24%, 26%, 28%, and 30%; and a porogen, comprising 15-20%, specifically, but not limited to, 15%, 16%, 17%, 18%, 19%, and 20%.
[0124] In a preferred embodiment of the present invention, the method for preparing the anal fistula repair component further includes the following steps: loading a regeneration repair regulator, an immunomodulator, and an antibiotic onto the first layer, the second layer, and the third layer respectively by means of impregnation or spraying.
[0125] In the preferred embodiment described above, the process of loading the regenerative repair modifier, immunomodulator, and antibiotic into the first, second, and third layers, respectively, can be done during the production of the anal fistula repair component, or it can be added by the doctor based on the patient's condition during use of the component. Adding the modifier by the doctor based on the patient's condition during use helps avoid drug allergies and allows for the selection of more suitable regenerative repair modifiers, immunomodulators, or antibiotics for the patient.
[0126] The specific operation is as follows: (1) Select a suitable solvent, such as physiological saline or PBS solution, and prepare the regeneration repair regulator, immunomodulator or antibiotic solution into a concentration suitable for human absorption and use.
[0127] (2) Add the first layer, the second layer, and the third layer to the regeneration repair regulator solution, the immunoregulator solution, and the antibiotic solution respectively, and soak for a few seconds, preferably within 10 seconds.
[0128] Alternatively, the regeneration and repair regulator solution, immune regulator solution, and antibiotic solution can be sprayed or applied to the surface of the first layer (facing the second layer), the surface of the second layer (facing the third layer), or the surface of the third layer (away from the second layer), respectively.
[0129] According to one aspect of the present invention, a method of using an anal fistula repair component is provided, comprising the following steps: winding a first sheet one or more turns to form a columnar or conical inner layer;
[0130] The second layer is attached to the outside of the inner layer and rolled up one or more times to form a columnar or conical outer layer.
[0131] The columnar or conical body formed by the first and second layers nested together is the absorbable anal fistula repair body;
[0132] The absorbable anal fistula repair body is used for implantation into the fistula tract.
[0133] Preferably, a third layer is rolled up outside the outer layer, and the third layer is attached to the outer layer and rolled up one or more times to form a columnar or conical outermost layer.
[0134] The method of using the anal fistula repair component provided by this invention involves sequentially rolling the first and second independent layers of the component into a cylindrical or conical shape to form an absorbable anal fistula repair body, which is then implanted into the fistula tract. Specifically, before implanting into the fistula tract, rolling each layer to create the absorbable anal fistula repair body allows doctors to easily prepare absorbable anal fistula repair bodies of appropriate size, shape, and number to implant into one or more branch fistula tracts based on the patient's fistula diameter, number, and direction, without being limited by the inherent diameter, length, or curvature of standard specifications. Furthermore, the absorbable anal fistula repair body made from the anal fistula repair component is flexible, easy to bend, and convenient to implant into the fistula tract.
[0135] In the repair of anal fistulas, the first and second layers together form a columnar or conical absorbable fistula repair body. The first layer is rolled up one or more times to form a columnar or conical inner layer; the second layer is also rolled up one or more times, forming a columnar or conical shape, located outside the inner layer. The first and second layers are not tightly adhered; there are gaps between them. When the first or second layer is rolled up multiple times, there are also gaps between adjacent turns. Purulent fluid, inflammatory exudate, bloody secretions, and other substances drain out of the fistula tract through these gaps. Drainage promotes fistula healing, and combined with antibacterial, anti-inflammatory drug preparations and regenerative repair agents, the fistula repair effect is even better.
[0136] It is important to note that after the first and second layers are rolled into a cylindrical or conical shape, their shape does not need to be fixed. When the second layer wraps around the first layer to form a new cylindrical or conical shape, the rolled first layer freely opens up and contacts the rolled second layer, but with a gap. This gap serves as drainage during fistula repair. When an absorbable fistula repair device with first and second layers is implanted into the fistula tract, because the second layer is not fixed in shape, it freely opens up within the fistula tract and contacts the fistula wall, but with a gap. This gap also serves as drainage during fistula repair. If the first or second layer is rolled multiple times, there are gaps between the layers, which also serve as drainage during fistula repair.
[0137] Similarly, in a preferred embodiment of the present invention, in the absorbable anal fistula repair body in which the third layer is rolled over the second layer, it is not necessary to fix the shape of the first, second, and third layers. If each layer is rolled up in multiple turns, there are gaps between the layers, gaps between each layer, and gaps between the third layer and the fistula wall. All of the above gaps can play a drainage role in the anal fistula repair process.
[0138] In a preferred embodiment, before rolling the first, second, or third layer, the regeneration and repair regulators, immunomodulators, and antibiotics required for each layer are loaded into the layers by means of soaking, spraying, or applying. This loading at this stage allows doctors to conveniently select specific drugs or preparations, as well as specific concentrations, based on the patient's condition, without being limited by inherent specifications.
[0139] According to one aspect of the present invention, an anal fistula repair material is provided, which is an absorbable anal fistula repair body obtained by using the above-described anal fistula repair component and the above-described method of use.
[0140] If the absorbable anal fistula repair component has poor mechanical properties, it will be unable to withstand pressure changes within the intestines and external forces caused by the patient's daily activities during the fistula repair process after implantation. This can easily lead to deformation, displacement, damage, or collapse, affecting the fistula repair outcome. Therefore, the absorbable anal fistula repair component needs to have good overall mechanical properties. To ensure this, the first layer, which is the last to degrade in the anal fistula repair component of this patent, plays a crucial role in providing mechanical support. The first layer of the anal fistula repair component in this patent has excellent mechanical properties, ensuring sufficient mechanical support required for clinical use.
[0141] In a preferred embodiment of the present invention, the maximum tensile force of the first layer of the anal fistula repair component reaches 26.34 N or more, the elastic modulus reaches 284.29 MPa or more, and the elongation at break reaches 493.25% or more.
[0142] According to one aspect of the present invention, the above-described anal fistula repair component, or the anal fistula repair component prepared by the above-described preparation method, or the above-described anal fistula repair material is used in the preparation of instruments and drugs for treating anal fistulas.
[0143] In addition to being used alone for anal fistula repair, in a preferred embodiment of the present invention, the anal fistula repair component can also be used in combination with other instruments and drugs for treating anal fistulas.
[0144] In the following specific embodiments, the biodegradable material used to fabricate the patch is a PCL-PEG copolymer (which is also a biodegradable polyurethane) formed by copolymerizing polycaprolactone (PCL) and polyethylene glycol (PEG), and can be prepared according to the manufacturing method in the embodiment of patent 202111122492.8. Other materials used in the embodiments were purchased directly from the market.
[0145] The anal fistula repair component of this invention has good biocompatibility. In particular, the anal fistula repair component made of a copolymer of polycaprolactone (PCL) and polyethylene glycol (PEG) has excellent biocompatibility. After implantation into the human body, there is no immune rejection reaction. During the process of complete degradation and absorption in the body, the degradation products are non-toxic and the pH changes little, which greatly reduces the risk of inflammation caused by patch implantation. The local microenvironment is stable and conducive to tissue regeneration.
[0146] Example 1
[0147] In this embodiment, the anal fistula repair component comprises two sheets, both prepared using a casting method, without any drugs or preparations loaded. The specific preparation method includes:
[0148] 1. Create the first layer
[0149] Preparation of the first sheet preparation solution: Grind sodium chloride (porogen) and sieve to obtain sodium chloride particles with a size of 1-350 μm. Dissolve the biodegradable material (weight-average molecular weight Mw of 180 kDa) in tetrahydrofuran (THF), then add sodium chloride and stir magnetically until the sodium chloride is uniformly dispersed in the solution to prepare the first sheet preparation solution. This solution consists of the following components by mass percentage: 25% biodegradable material, 5% sodium chloride, and the balance being tetrahydrofuran.
[0150] Coating and forming: Pour the first layer preparation solution onto a glass plate, place the coating applicator with the height adjusted (0.5 mm), push it open with an automatic coating machine, and air dry under a laminar flow hood.
[0151] Impurity removal and drying: After soaking in water for injection for 10 days (to remove solvent and pore-forming agent), the first sheet is dried at 35°C to obtain the first sheet.
[0152] 2. Create the second layer
[0153] Preparation of the second layer preparation solution: Grind sodium chloride and sieve to obtain sodium chloride particles with a size of 50-350 μm. Dissolve the biodegradable material (weight-average molecular weight Mw of 40 kDa) in tetrahydrofuran (THF), then add sodium chloride and stir magnetically until the sodium chloride is uniformly dispersed in the solution to prepare the second layer preparation solution. This solution consists of the following components by mass percentage: 25% biodegradable material, 10% sodium chloride, and the balance being tetrahydrofuran.
[0154] Coating and forming: Pour the solution for making the second layer onto a glass plate, place the coating applicator with the height adjusted (0.2 mm), push it open with an automatic coating machine, and air dry under a laminar flow hood.
[0155] Impurity removal and drying: After soaking in water for injection for 10 days (to remove solvent and pore-forming agent), the second layer is dried at 35°C to obtain the second layer.
[0156] 3. Post-treatment of anal fistula repair components
[0157] In this embodiment, the anal fistula repair component consists of two independently formed layers: a first layer and a second layer.
[0158] Remove any rough edges or uneven thickness from the first and second sheets obtained in the above steps. Ensure there are no air bubbles, breaks, or foreign objects, and that the sheets are of uniform thickness. Cut them to the required dimensions. Sterilize using cobalt-60 gamma ray irradiation, package, and store.
[0159] Example 2
[0160] In this embodiment, the anal fistula repair component comprises two sheets, both prepared by electrospinning, without any drugs or preparations loaded. The specific preparation method includes:
[0161] 1. Create the first layer
[0162] (1) Preparation of the first layer electrospinning solution:
[0163] A first-layer electrospinning solution was prepared using a biodegradable material (weight-average molecular weight Mw of 180 kDa) as the solute and a mixed solution of tetrahydrofuran (THF) and N,N-dimethylformamide (DMF) as the solvent. The solution consisted of the following components by mass percentage: 25% biodegradable material, 5% sodium chloride (1-350 μm particle size), and the remainder being solvent.
[0164] The ratio of each component in the solvent is: tetrahydrofuran (THF): N,N-dimethylformamide (DMF) = 1:1.
[0165] The specific preparation steps are as follows:
[0166] 1) Measure 150 mL of tetrahydrofuran and 150 mL of N,N-dimethylformamide into a three-necked flask, turn on the stirrer, adjust the speed to (200±100) r / min, and stir until homogeneous.
[0167] 2) Weigh 75g of the biodegradable material and add it to a three-necked flask. Different volumes of solution can be prepared depending on the amount of solution needed.
[0168] 3) Stir at room temperature for at least 4 hours to ensure complete dissolution of the biodegradable material. Let stand for at least 4 hours to remove air bubbles before use.
[0169] (2) Electrospinning:
[0170] 1) Wipe the electrospinning machine clean to ensure the equipment is in a clean state.
[0171] 2) Secure the release paper to the receiving device, ensuring that the release paper does not loosen.
[0172] 3) Adjust the distance between the nozzle and the receiver to 20±1 cm, confirm the position and tighten it.
[0173] 4) The receiver rotation speed is set to (300±100) rpm / min; the nozzle injection speed is set to 0.4±0.05ml / min.
[0174] 5) The translation speed of the nozzle is set to 400±50 mm / min, and the translation distance is set to 200±50 mm.
[0175] 6) Using the prepared 25% biodegradable material solution, slowly draw the solution with a disposable syringe to avoid generating air bubbles. If air bubbles are generated, they must be removed before proceeding with subsequent operations. Attach a 22G needle (0.41mm inner diameter) and secure the syringe to the electrospinning machine's injection pump clip.
[0176] The nozzle diameter can be selected from 0.15 to 4.2 mm, preferably using 18G (0.9 mm inner diameter), 19G (0.84 mm inner diameter), 20G (0.62 mm inner diameter), 21G (0.51 mm inner diameter), 22G (0.41 mm inner diameter), 23G (0.33 mm inner diameter), or 24G (0.3 mm inner diameter) needles. In this embodiment, a 22G needle is selected.
[0177] 7) Set the negative voltage to (-3±1) KV and the positive voltage to (9±0.5) KV. Start electrospinning and observe the spinning effect until continuous and uniform filaments are produced. Set the electrospinning time to 4.5 hours. After electrospinning is completed, remove the electrospun film from the release paper; this is the first sheet of the initial product.
[0178] (3) Post-processing:
[0179] 1) Soak the above electrospun membrane in a water tank for at least 7 days, changing the water twice a day and cleaning it every two days to remove solvent residue from the above electrospun membrane.
[0180] The ratio of patch surface area to water volume in each water tank should be ≥900 cm². 2 / L.
[0181] 2) Rinse the electrospun film with water for injection cooled to 30°C, and lay it flat on the rack of the drying oven.
[0182] The oven temperature was set at 35℃, and the drying time was (5±1) h. After the electrospun film was dried, an appearance inspection was performed, and then it was cut into the first layer of the required size.
[0183] 2. Create the second layer
[0184] (1) Preparation of the electrospinning solution for the second layer:
[0185] A second-layer electrospinning solution was prepared using a biodegradable material (weight-average molecular weight Mw of 40 kDa) as the solute and a mixed solution of tetrahydrofuran (THF) and N,N-dimethylformamide (DMF) as the solvent. The solution consisted of the following components by mass percentage: 25% biodegradable material, 10% sodium chloride (50-350 μm particle size), and the remainder being solvent.
[0186] The ratio of each component in the solvent is: tetrahydrofuran (THF): N,N-dimethylformamide (DMF) = 1:1.
[0187] The specific preparation steps are as follows:
[0188] 1) Measure 150 mL of tetrahydrofuran and 150 mL of N,N-dimethylformamide into a three-necked flask, turn on the stirrer, adjust the speed to (200±100) r / min, and stir until homogeneous.
[0189] 2) Weigh 75g of biodegradable material and add it to a three-necked flask; different volumes of solution can be prepared according to the amount of solution to be used.
[0190] 3) Stir at room temperature for at least 4 hours to ensure complete dissolution of the biodegradable material. Let stand for at least 4 hours to remove air bubbles before use.
[0191] (2) Electrospinning:
[0192] The specific operation steps are the same as those in “(2) electrospinning” in “1. Making the first layer” of this embodiment, electrospinning for 2 hours.
[0193] (3) Post-processing:
[0194] The specific operation steps are the same as the "(3) post-processing" operation steps in "1. Making the first layer" of this embodiment.
[0195] 3. Post-treatment of anal fistula repair components
[0196] In this embodiment, the anal fistula repair component consists of two independently formed layers: a first layer and a second layer.
[0197] Remove any rough edges or uneven thickness from the first and second sheets obtained in the above steps. Ensure there are no air bubbles, breaks, or foreign objects, and that the sheets are of uniform thickness. Cut them to the required dimensions. Sterilize using cobalt-60 gamma ray irradiation, package, and store.
[0198] Example 3
[0199] In this embodiment, the anal fistula repair component comprises three layers, all prepared using a casting method. The third layer contains antibiotics, while the first and second layers do not contain any drugs or preparations. The specific preparation method includes:
[0200] The preparation method of the anal fistula repair component in this embodiment differs from that in Embodiment 1 in that, in addition to making the first layer and the second layer, a third layer is also made in this embodiment.
[0201] 1. Create the first layer and the second layer.
[0202] The manufacturing methods for the first and second layers are the same as in Example 1.
[0203] 2. Create the third layer
[0204] The specific method for creating the third layer is as follows:
[0205] Preparation of the third layer preparation solution: Grind sodium chloride and sieve to obtain sodium chloride particles with a size of 1-200 μm. Dissolve the biodegradable material (weight-average molecular weight Mw of 8 kDa) in tetrahydrofuran (THF), then add sodium chloride and stir magnetically until the sodium chloride is uniformly dispersed in the solution to prepare the third layer preparation solution. This solution contains: 25% biodegradable material, 15% sodium chloride (1-200 μm particle size), and the balance is tetrahydrofuran (by mass percentage).
[0206] Coating and forming: Pour the solution for making the third layer onto a glass plate, place the coating applicator with the height adjusted (0.1 mm), push it open with an automatic coating machine, and air dry under a laminar flow hood.
[0207] Impurity removal and drying: After soaking in water for injection for 10 days (to remove solvent and pore-forming agent), dry at 35°C to obtain the third layer of the initial product.
[0208] 3. Post-treatment of anal fistula repair components
[0209] In this embodiment, the anal fistula repair component consists of three independently formed layers: a first layer, a second layer, and a third layer. Figure 1 As shown, from left to right, they are the third layer, the second layer, and the first layer.
[0210] Remove any rough edges or uneven thickness from the first, second, and third sheets prepared in the above steps. Ensure there are no air bubbles, damage, or foreign objects, and that the sheets are of uniform thickness. Cut them to the required dimensions. Sterilize using cobalt-60 gamma irradiation, package, and store.
[0211] 4. The third layer contains antibiotics:
[0212] Dissolve ciprofloxacin in physiological saline to prepare a saturated solution. Spray the saturated ciprofloxacin solution evenly onto one side of the third layer of the initial product, ensuring the surface is moistened but not dripping. Note that the side sprayed with ciprofloxacin should be marked. When using the fistula repair component and rolling the third layer later, the side sprayed with the saturated ciprofloxacin solution should be the side furthest from the second layer.
[0213] Example 4
[0214] In this embodiment, the anal fistula repair component comprises three layers, all prepared using a casting method. The third layer is loaded with antibiotics, the first layer with a regeneration and repair regulator, and the second layer with an immunomodulator. The specific preparation method includes:
[0215] The preparation method of the anal fistula repair component in this embodiment is the same as that in embodiment 3. The preparation methods of the first layer, the second layer and the third layer are the same. The difference is that the first layer in this embodiment carries a regeneration and repair regulator, specifically basic fibroblast growth factor, and the second layer carries an immunomodulator, specifically infliximab.
[0216] Specifically:
[0217] The first layer is infused with basic fibroblast growth factor (BGF): Based on the clinically required dosage, evenly spray a commercially available BGF solution onto one side of the first layer. The amount sprayed should be just enough to moisten the surface without dripping. It is important to mark the side sprayed with BGF. When using the fistula repair kit and rolling up the first layer, the side saturated with BGF solution should face the second layer.
[0218] The second layer is loaded with infliximab: Based on the required clinical dosage, prepare an infliximab solution and spray it evenly onto one side of the second layer. The amount sprayed should be just enough to moisten the surface without dripping. It is important to mark the side sprayed with infliximab. When using the fistula repair kit and rolling up the second layer, the side saturated with the infliximab solution should face the third layer.
[0219] Example 5: Use of the anal fistula repair component from Example 1
[0220] Includes the following steps:
[0221] Roll the first layer around twice to form a columnar inner layer;
[0222] The second layer is attached to the outside of the inner layer and rolled up twice to form a columnar outer layer.
[0223] The columnar body formed by the sequential nesting of the first and second tubular layers constitutes the absorbable anal fistula repair. This absorbable anal fistula repair can be implanted into the fistula tract.
[0224] Example 6: Use of the anal fistula repair component in Example 2
[0225] Includes the following steps:
[0226] Roll the first layer around twice to form a columnar inner layer;
[0227] The second layer is attached to the outside of the inner layer and rolled up twice to form a columnar outer layer.
[0228] The columnar body formed by the sequential nesting of the first and second tubular layers constitutes the absorbable anal fistula repair. This absorbable anal fistula repair can be implanted into the fistula tract.
[0229] Example 7: Use of the anal fistula repair component from Example 3
[0230] Includes the following steps:
[0231] Roll the first layer around twice to form a columnar inner layer;
[0232] The second layer is attached to the outside of the inner layer and rolled up twice to form a columnar outer layer.
[0233] The third layer is attached to the outside of the outer layer and rolled up twice to form the outermost columnar layer.
[0234] The columnar body formed by the sequential nesting of the first, second, and third layers constitutes the absorbable anal fistula repair body. Figure 2 As shown. This absorbable anal fistula repair can be used for implantation into the fistula tract.
[0235] Example 8: Use of the anal fistula repair component from Example 4
[0236] Includes the following steps:
[0237] Roll the first layer around twice to form a columnar inner layer;
[0238] The second layer is attached to the outside of the inner layer and rolled up twice to form a columnar outer layer.
[0239] The third layer is attached to the outside of the outer layer and rolled up twice to form the outermost columnar layer.
[0240] The columnar body formed by the sequential nesting of the first, second, and third layers constitutes the absorbable anal fistula repair. This absorbable anal fistula repair can be implanted into the fistula tract.
[0241] Experimental Example 1
[0242] 1. Mechanical property testing
[0243] Experimental methods:
[0244] The first layer of the anal fistula repair component in Examples 1-4 and the absorbable anal fistula repair body in Examples 5-8 were cut into multiple samples of appropriate length. Then, the tensile testing machine was turned on, the parameters were set, the test was carried out, and various data were processed to calculate the average value.
[0245] (1) Maximum tensile force and elastic modulus: Turn on the tensile testing machine, set the parameters, and perform tensile strength test on the specimen. The maximum force during the tensile fracture process is recorded as the maximum tensile force, and the elastic modulus is obtained by data processing.
[0246] (2) Elongation at break: Turn on the tensile testing machine, set the parameters, test the elongation at break of the specimen, and process the data. The elongation at break (%) = (elongation at break of specimen / original length of specimen) × 100%.
[0247] The experimental results are shown in Table 1 below:
[0248] Table 1. Summary of Mechanical Property Tests for Examples 1-8
[0249]
[0250]
[0251] The results above show that the maximum tensile force of the first layer of the anal fistula repair component of the present invention reaches 26.34 N or more, the elastic modulus reaches 284.29 MPa or more, and the elongation at break reaches 493.25% or more. When used, the anal fistula repair component of the present invention exhibits the following characteristics: the maximum tensile force of the absorbable anal fistula repair body reaches 39.27 N or more, the elastic modulus reaches 340.32 MPa or more, and the elongation at break reaches 897.91% or more.
[0252] The anal fistula repair component of this invention—an absorbable anal fistula repair body—possibly provides sufficient mechanical strength to meet the mechanical performance requirements of absorbable anal fistula repair bodies during the repair process. Furthermore, the first layer of this invention's anal fistula repair component exhibits excellent mechanical properties; even with only the first layer, it can still provide the necessary mechanical support strength for the anal fistula repair process.
[0253] Meanwhile, the absorbable anal fistula repair body prepared by this invention has an elastic modulus of 340.32 MPa. The absorbable anal fistula repair body is soft and elastic, which can greatly reduce tissue damage during implantation, reduce patient discomfort, and improve patient acceptance.
[0254] 2. Degradation experiment
[0255] Experimental methods:
[0256] (1) Preparation of enzyme buffer:
[0257] Prepare a buffer solution containing potassium dihydrogen phosphate and disodium hydrogen phosphate using sterile double-distilled water. Each liter of buffer solution contains 1.653 g KH₂PO₄ and 7.744 g Na₂HPO₄. The pH of the buffer solution should be 7.4 ± 0.2. After sterilization, add 0.2 g / L lipase.
[0258] The salt used in the preparation was of analytical grade and dried to constant weight.
[0259] (2) Degradation test:
[0260] Cut the first, second, and third layers of the anal fistula repair components from Examples 1-4 into multiple samples of appropriate sizes, vacuum dry them at room temperature to constant weight, and accurately measure the weight of the samples. Place the samples in glass containers, cover them with enzyme buffer, and seal the containers. The minimum volume of the buffer should be 10 ml, and the ratio of buffer volume (ml) to sample mass (g) should be greater than or equal to 30:1. Maintain the samples at 37±1℃ using a constant temperature water bath or oven.
[0261] Degradation cycle determined:
[0262] The degradation test of the first layer sample was conducted by taking samples at 11, 12, 14, 16, 18, 20, 22, 24, 26 and 27 weeks for mechanical property testing.
[0263] The degradation test of the second layer sample was conducted by taking samples at 3, 4, 6, 8, 10, 12 and 13 weeks for mechanical property testing.
[0264] The degradation test of the third layer sample was conducted by taking samples at 1 week, 2 weeks, 3 weeks, 4 weeks and 5 weeks for mechanical property testing.
[0265] After wiping the liquid off the sample surface with a paper towel, place the sample into the tensile testing machine fixture and conduct the test directly. Set the testing rate to 50 mm / min. The test will be terminated when the sample can no longer be tested for mechanical properties; the point at which the test stops is the sample's degradation cycle.
[0266] The obtained degradation cycle data are shown in Table 2 below.
[0267] Table 2. Summary of degradation times for different lamellar layers
[0268]
[0269] As can be seen from the above data, the complete degradation time of the third layer of the anal fistula repair component prepared in the various embodiments of the present invention is 2 weeks and 4 weeks; the complete degradation time of the second layer is 6 weeks, 8 weeks, 10 weeks and 12 weeks; and the complete degradation time of the first layer is 16 weeks, 18 weeks, 22 weeks and 26 weeks. This ensures that sufficient support is provided during the anal fistula healing period, that premature degradation does not affect the anal fistula repair, and that the component gradually degrades after the anal fistula heals without causing additional discomfort or risk to the patient.
[0270] 3. Antibacterial performance test
[0271] Test sample:
[0272] The third layer of the anal fistula repair component in Examples 3 and 4, and multiple samples of the absorbable anal fistula repair body in Examples 7 and 8.
[0273] Test method:
[0274] (1) Test subjects: Escherichia coli and Staphylococcus aureus.
[0275] (2) Test method: antibacterial test.
[0276] (3) Under aseptic conditions, each sample was cut into small pieces and then placed into a medium inoculated with Escherichia coli or Staphylococcus aureus. The samples were incubated at 37°C for 24 h, 3 d, and 7 d, and colony counts were performed.
[0277] The formula for calculating the antibacterial rate is: X = (AB) / A × 100%, where X is the antibacterial rate, A is the average number of colonies before the sample is shaken, and B is the average number of colonies after the sample is shaken.
[0278] (4) Test results
[0279] The test results are shown in Table 3 below (all tests were performed three times, and the average value was taken):
[0280] Table 3. Summary of antibacterial properties of Examples 3, 4, 7, and 8
[0281]
[0282] As can be seen from the above data, the third layer of the anal fistula repair component prepared in the embodiments of the present invention carries antibiotics and has a significant antibacterial effect.
[0283] 4. Cell proliferation experiment
[0284] Experimental methods:
[0285] The second layer of the anal fistula repair component in Examples 1 and 2 was made into a 48-hole plate with a bottom area of 1 cm² using a punch. 2 The circular samples were sterilized by irradiation at 25 KGy, and then each sample was immersed in MEM medium containing 10% FBS at 37°C and 60 rpm for 24 h.
[0286] The entire procedure was performed in a clean bench to ensure aseptic operation. Mouse fibroblasts L-929 cells grown to the logarithmic growth phase were digested with 0.25% trypsin (containing EDTA). After digestion, the cell suspension was centrifuged (1000 rpm, 5 min), the supernatant was discarded, and the cells were resuspended in MEM medium. Cells were counted to obtain 5 × 10⁶ cells per cell. 4 Prepare a cell suspension of cells / mL; spread each soaked sample evenly in a 48-well plate, and perform three parallel operations on each group.
[0287] 5×10 4 Cell suspension of 300 μL per well was seeded into two other 48-well plates. The same procedure was performed on two other 48-well plates, and the plates were cultured in a cell culture incubator (37°C, 5% CO2, >90% humidity).
[0288] After 24 hours, 3 days, and 6 days, the original culture medium in the 48-well plates was discarded. 100 μL of MTT (final concentration 1 mg / mL) was added to the corresponding wells of each 48-well plate, and the plates were incubated in a CO2 incubator. After 2 hours, the supernatant was removed, and 200 μL of isopropanol was added to each well to dissolve the crystals. After the crystals were completely dissolved, the samples were removed, and the liquid in each well was transferred to a 96-well plate, 100 μL per well. The absorbance value at 570 nm was measured on a microplate reader, and the OD value was compared with that of the blank group to determine whether the cells had a proliferation effect on the material surface, and the cell proliferation rate was calculated.
[0289] The specific test results are shown in Table 4 below:
[0290] Table 4. Results of cell proliferation experiment
[0291]
[0292] As can be seen from the above data, the second layer of the anal fistula repair component prepared in the embodiments of the present invention has a good cell proliferation rate effect.
[0293] The undescribed parts of this invention are the same as or implemented using existing technology. The applicant declares that this invention is illustrated through the above embodiments, but the invention is not limited to the above detailed methods, i.e., it does not mean that the invention must rely on the above detailed methods to be implemented. Those skilled in the art should understand that any improvements to this invention, equivalent substitutions of raw materials for the product of this invention, additions of auxiliary components, and selection of specific methods all fall within the protection and disclosure scope of this invention.
Claims
1. A fistula repair component, characterized in that, It comprises three independently formed sheets: a first sheet, a second sheet, and a third sheet, all made of biodegradable materials. The first layer is a porous structure with a thickness of 0.1-0.5 mm, a pore size ranging from 1-350 μm, a porosity of 10-20%, and a degradation time of 12-26 weeks post-surgery. The second layer is a porous structure with a thickness of 0.05-0.2 mm, a pore size ranging from 50-350 μm, a porosity of 20-35%, and a degradation time of 4-12 weeks post-surgery. The third layer is a porous structure with a thickness of 0.05-0.1 mm, a pore size ranging from 1-200 μm, and a porosity of 30-45%. Its degradation time is from the 2nd to the 4th week after surgery. The first layer carries a regeneration and repair regulator, the second layer carries an immunomodulator, and the third layer carries an antibiotic. The regeneration and repair regulator is selected from any one or more combinations of thymopentin, basic fibroblast growth factor, epidermal growth factor, vascular endothelial growth factor, concentrated growth factor, transforming growth factor-β1, or mesenchymal stem cells. The immunomodulatory agent is selected from any one or more combinations of infliximab, adalimumab, ustekinumab, vedolizumab, sertozumab, methotrexate, azathioprine, or 6-mercaptopurine. The antibiotic is selected from any one or more combinations of ciprofloxacin, metronidazole, gentamicin, erythromycin, mupirocin, or levofloxacin. The preparation method of the anal fistula repair component is as follows: The first layer, the second layer, and the third layer are fabricated separately, including the following steps: (a) Dissolve the biodegradable material in a solvent, add a pore-forming agent, and obtain a biodegradable material solution. (b) Using electrospinning or casting methods, the first layer, second layer, or third layer are fabricated respectively. (c) Remove solvent and dry. When making the first layer, the pore-forming agent has a particle size of 1-350μm, and the biodegradable material solution is composed of the following components by mass percentage: 10-30% biodegradable material and 5-10% pore-forming agent, with the remainder being solvent. When making the second layer, the pore-forming agent has a particle size of 50-350μm. The biodegradable material solution is composed of the following components by mass percentage: 10-30% biodegradable material and 10-15% pore-forming agent, with the remainder being solvent. When fabricating the third layer, the porogen particle size is 1-200 μm. The biodegradable material solution consists of the following components by mass percentage: 10-30% biodegradable material, 15-20% porogen, and the remainder is solvent. When in use, the anal fistula repair component involves rolling the first layer one or more times to form a columnar or conical inner layer; then attaching the second layer to the outside of the inner layer and rolling it one or more times to form a columnar or conical outer layer; the columnar or conical body formed by the first and second layers in sequence is the absorbable anal fistula repair body, which is used for implantation into the fistula tract; a third layer is also rolled around the outside of the outer layer, and the third layer is attached to the outside of the outer layer and rolled one or more times to form a columnar or conical outermost layer.
2. The anal fistula repair component according to claim 1, characterized in that: The biodegradable material includes any one or more copolymers or combinations thereof selected from biodegradable polyurethane, polylactic acid, polyglycolic acid, polycaprolactone, polyethylene glycol, polyvinyl alcohol, polycarbonate, polyhydroxyalkanoates, polyanhydrides, polydioxanone, or bacterial cellulose.
3. The anal fistula repair component according to claim 2, characterized in that: The biodegradable material used to fabricate the first layer is selected from any one or more copolymers or combinations thereof from the group consisting of: biodegradable polyurethane with a weight-average molecular weight of 50k-280kDa, polylactic acid with a weight-average molecular weight of 50k-200kDa, polyglycolic acid with a weight-average molecular weight of 50k-200kDa, polycaprolactone with a weight-average molecular weight of 40k-200kDa, polyethylene glycol with a weight-average molecular weight of 20k-80kDa, polyvinyl alcohol with a weight-average molecular weight of 30k-100kDa, polycarbonate with a weight-average molecular weight of 40k-120kDa, polyhydroxyalkanoates with a weight-average molecular weight of 100k-200kDa, polyanhydrides with a weight-average molecular weight of 20k-50kDa, polydioxanone with a weight-average molecular weight of 80k-300kDa, and poly(p-dioxanone) with a weight-average molecular weight of 300k-800kDa. Bacterial cellulose, a copolymer of polycaprolactone and polyethylene glycol with a weight-average molecular weight of 50k-280kDa. The biodegradable material used to make the second layer is selected from any one or more copolymers or combinations of the following group: biodegradable polyurethane with a weight-average molecular weight of 20k-80kDa, polylactic acid with a weight-average molecular weight of 15k-80kDa, polyglycolic acid with a weight-average molecular weight of 20k-80kDa, polycaprolactone with a weight-average molecular weight of 15k-50kDa, polyethylene glycol with a weight-average molecular weight of 10k-25kDa, polyvinyl alcohol with a weight-average molecular weight of 15k-50kDa, polycarbonate with a weight-average molecular weight of 15k-50kDa, polyhydroxyalkanoates with a weight-average molecular weight of 40k-120kDa, polyanhydrides with a weight-average molecular weight of 15k-30kDa, polydioxanone with a weight-average molecular weight of 20k-60kDa, bacterial cellulose with a weight-average molecular weight of 100k-300kDa, and copolymers of polycaprolactone and polyethylene glycol with a weight-average molecular weight of 20k-80kDa. The biodegradable material used to make the third layer is selected from any one or more copolymers or combinations of the following: biodegradable polyurethane with a weight average molecular weight of 8k-30kDa, polylactic acid with a weight average molecular weight of 8k-20kDa, polyglycolic acid with a weight average molecular weight of 8k-30kDa, polycaprolactone with a weight average molecular weight of 5k-20kDa, polyethylene glycol with a weight average molecular weight of 8k-15kDa, polyvinyl alcohol with a weight average molecular weight of 5k-20kDa, polycarbonate with a weight average molecular weight of 5k-20kDa, polyhydroxyalkanoates with a weight average molecular weight of 8k-25kDa, polyanhydrides with a weight average molecular weight of 8k-20kDa, polydioxanone with a weight average molecular weight of 10k-25kDa, bacterial cellulose with a weight average molecular weight of 40k-150kDa, and copolymers of polycaprolactone and polyethylene glycol with a weight average molecular weight of 8k-30kDa.
4. The anal fistula repair component according to claim 1, characterized in that, It also includes the following steps: Regeneration and repair modifiers, immunomodulators, and antibiotics are loaded onto the first, second, and third layers respectively by impregnation or spraying.
5. The use of the anal fistula repair component according to any one of claims 1 to 4 in the preparation of an instrument for treating anal fistula.
Citation Information
Patent Citations
Degradable polyurethane biological material as well as preparation method and application thereof
CN109851744A
Preparation method and application of organic metal catalyst and degradable biological material
CN115521430A
A device for treating a fistula
AU2023364126A1
Fistula restoration promoting material and preparation method thereof
CN104491933A